2016
DOI: 10.1371/journal.pone.0141438
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Radiation-Induced Necrosis from Recurrent Brain Tumor Using MR Perfusion and Spectroscopy: A Meta-Analysis

Abstract: PurposeThis meta-analysis examined roles of several metabolites in differentiating recurrent tumor from necrosis in patients with brain tumors using MR perfusion and spectroscopy.MethodsMedline, Cochrane, EMBASE, and Google Scholar were searched for studies using perfusion MRI and/or MR spectroscopy published up to March 4, 2015 which differentiated between recurrent tumor vs. necrosis in patients with primary brain tumors or brain metastasis. Only two-armed, prospective or retrospective studies were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 43 publications
4
136
0
1
Order By: Relevance
“…However, to date none of these scan types can reliably distinguish radiation necrosis from tumor progression based on lesion appearance (Figure 1). Other special imaging approaches [6; 7] may be useful to distinguish radiation necrosis from tumor progression, but they are not generally available.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date none of these scan types can reliably distinguish radiation necrosis from tumor progression based on lesion appearance (Figure 1). Other special imaging approaches [6; 7] may be useful to distinguish radiation necrosis from tumor progression, but they are not generally available.…”
Section: Introductionmentioning
confidence: 99%
“…As techniques develop and more research is conducted, multimodal imaging may become more widely used. Chuang et al [38] previously performed a meta-analysis to differentiate radiation-induced necrosis from recurrent brain tumors by magnetic resonance perfusion and spectroscopy. They included patients with primary brain tumor as well as those with brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study using DCE perfusion data found that a plasma–volume ratio ≥ 2.6 identified progression versus radiation treatment effect with sensitivity of 91% and specificity of 80% (Hatzoglou et al, 2015). Although perfusion MRI-based rCBV appears more accurate than MRS (Huang et al, 2011), a meta-analysis has shown that both rCBV and Cho/Cr help differentiate true progression from radiation necrosis (Chuang et al, 2016). …”
Section: Caveats To Interpreting Posttreatment Imaging Changesmentioning
confidence: 99%